2008
DOI: 10.1002/ibd.20511
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of quality of life and psychological functioning for active, fluctuating, and inactive disease patterns in inflammatory bowel disease

Abstract: Change in IBD QOL is influenced by one's longitudinal profile of disease activity, but change in psychological functioning is not. Effects of disease activity on psychological functioning were modest, suggesting that disease has an impact even when patients are not experiencing active symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
132
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 217 publications
(144 citation statements)
references
References 41 publications
9
132
0
3
Order By: Relevance
“…In previous research, using a community-based IBD sample and a broad assessment of psychological functioning, our team found that those with active IBD managed more poorly in multiple domains, experiencing higher levels of distress, health anxiety, and perceived stress, and lower psychological wellbeing and mastery, relative to those with inactive disease, both crosssectionally and across a two-year period 25,26 . Once disease activity was accounted for, there were no differences in these aspects of functioning between those with ulcerative colitis (UC) and CD.…”
Section: Introductionmentioning
confidence: 90%
“…In previous research, using a community-based IBD sample and a broad assessment of psychological functioning, our team found that those with active IBD managed more poorly in multiple domains, experiencing higher levels of distress, health anxiety, and perceived stress, and lower psychological wellbeing and mastery, relative to those with inactive disease, both crosssectionally and across a two-year period 25,26 . Once disease activity was accounted for, there were no differences in these aspects of functioning between those with ulcerative colitis (UC) and CD.…”
Section: Introductionmentioning
confidence: 90%
“…In fact, it has been found that depressed mood may stimulate the production of proinflammatory cytokines [16,17], modulating the clinical expression of IBD [6]. What is more, since increased IBD activity can influence the intensity of depression and anxiety experienced by patients [18][19][20], these mechanisms seem to unfold into a self-perpetuating cycle of psychological suffering and inflammation. It has thus 6 been pointed out that more priority to this subject should be given, and that more efforts should be made to uncover the mechanisms associated with the known effect of IBD symptomatology on depression [21].…”
Section: Inflammatory Bowel Disease and Psychological Distressmentioning
confidence: 99%
“…Sensitivity analyses 5-22: other deterministic sensitivity analyses (medical and surgical options) Table 83 presents the results of the remaining deterministic sensitivity analysis (analyses [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Assessment Group Model Resultsmentioning
confidence: 99%